Climatic conditions and sporadic permafrost in the Maiella Massif (Central Apennines, Italy) - BISCI C.; DRAMIS F.; GUGLIELMIN M.; FAZZINI, Massimiliano (Comitato Glaciologico Italiano:DIP Scienze Terra, V Acc Scienze 5, I 10123 Turin Italy:011 39 011 67007157, EMAIL: gfd@dstunivpi.it, Fax: 011 39 011 6707155, 2003)
Climatic data were examined for some ten weather recording stations, in order to verify the presence of favorable conditions for preserving sporadic mountain permafrost in the Maiella Massif (Central Apennines, Italy). The analyzed data refer to the time-span 1965-1990; they have been gathered for recording stations located at altitudes ranging from sea level (Pescara) to over 2100 m a.s.l. (Campo Imperatore, Gran Sasso Massif). The mean annual average temperatures were ca. 6-7 °C in the higher areas; the seasonal means ranged from –4 °C in winter to 12 °C in summer. Average thermal gradients vary from 0.4 °C/100 m in January to 0.7 °C/100 m in July, with an annual average of 0.57 °C/100 m. Based upon these data, the altitude of the 0 °C isotherm in free air in the Maiella Massif is ca. 2500 m, whilst the –2 °C isotherm, which can be used as the lower climatic limit for the presence of permafrost, should be located slightly over 2750 m a.s.l., on average. The precipitation regime generally has sub-Mediterranean features, which are progressively more evident moving from the Adriatic to the Tyrrhenian side. It shows a maximum in late autumn or winter and a minimum in summer, locally associated with a secondary maximum in late spring. Annual precipitation ranges around 1200-1400 mm, both in the high plains and on the main mountain peaks. Snow falls are abundant, especially along the eastern sides of the mountain groups, because of direct exposition to Balcanic-Danubian cold currents. At 1000 m a.s.l., generally 150 to 200 cm of snow fall are recorded and a snow blanket is present for ca. 70 days, concentrated in the November-April period; at ca. 2000 m a.s.l. (Campo Imperatore), the snow fall sums up to 400 cm and 180-200 days of persistence are recorded from the end of October to the end of May. Analyzing the above situation, it is possible to infer that the general climatic framework allows the presence of permafrost only close to the top of the Maiella Massif, at altitudes exceeding 2750 m a.s.l. On the other ...